How to prioritize patients and redesign care to safely resume planned surgery during the COVID-19 pandemic. (2021) - Logishetty, K.; Edwards, T. C.; Ponniah, H. Subbiah; Ahmed, M.; Liddle, A. D.; Cobb, J.; Clark, C.
No abstract available